2021
DOI: 10.3390/su13158121
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable I4.0: Key Skill Areas for Project Managers in GCC Construction Industry

Abstract: Industry 4.0 (I4.0) grew from and is guided by smart manufacturing. The fourth industrial revolution’s I4.0 would induce radical changes and transformations in the everyday operations of businesses and people’s life. Due to these major changes impacting all sectors and industries worldwide, the sustainability of the new future systems and operations is pertinent. The current research literature points out that the social (human factor) aspect is relatively underrepresented in the I4.0 sustainability-related st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Although researchers have identified various competencies that are needed for successfully managing projects, most of them identify these as lexical knowledge and skills. Moreover, these skills can be applied to both sustainability-focused and traditional projects, although in some cases, they should be enhanced with sustainability principles [42]. However, researchers all agree on the key role played by a project manager in achieving project success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although researchers have identified various competencies that are needed for successfully managing projects, most of them identify these as lexical knowledge and skills. Moreover, these skills can be applied to both sustainability-focused and traditional projects, although in some cases, they should be enhanced with sustainability principles [42]. However, researchers all agree on the key role played by a project manager in achieving project success.…”
Section: Discussionmentioning
confidence: 99%
“…Following Finn's [71] input competencies, numerous researchers have found that there may be two categories within project management competency: lexical knowledge and skill [2,8,79,109]. This can be valid for projects requiring special attitudes as well, such as sustainability [16,39,42,110]. Due to their popularity, we accepted the Project Management Institute's knowledge areas [111] and used them for further analysis.…”
Section: Research Goals and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved sales sector indication unfolds the communication for the customs or automated messages with data accessibility for the customers (Al Balushi et al, 2019). The marketing control and sales strategies implies for the altered sales growth which is to evaluate the strategies in a timely manner (Al Amri et al, 2021). The in-depth product services, experiences and the benefits are the realization of a SMEs relationship, which is reassuring the choice of customer in a reliable manner (Aljuwaiber, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is extremely beneficial to businesses in this technological era. Consequently, company collaboration may spur creativity and innovation, as well as develop novel ideas and concepts [44].…”
Section: Technology Transfer In the 40 Industrial Revolution And Open...mentioning
confidence: 99%